Multiple RNA virus matrix proteins interact with SLD5 to manipulate host cell cycle. (9th December 2021) - Zhu, Li; Li, Xinyu; Xu, Henan; Fu, Lifeng; Gao, George Fu; Liu, Wenjun; Zhao, Linqing; Wang, Xiaojun; Jiang, Wei; Fang, Min
Abstract : The matrix protein of many enveloped RNA viruses regulates multiple stages of viral life cycle and has the characteristics of nucleocytoplasmic shuttling. We have previously demonstrated that matrix protein 1 (M1) of an RNA virus, influenza virus, blocks host cell cycle progression by interacting with SLD5, a member of the GINS complex, which is required for normal cell cycle progression. In this study, we found that M protein of several other RNA viruses, including VSV, SeV and HIV, interacted with SLD5. Furthermore, VSV/SeV infection and M protein of VSV/SeV/HIV induced cell cycle arrest at G0/G1 phase. Importantly, overexpression of SLD5 partially rescued the cell cycle arrest by VSV/SeV infection and VSV M protein. In addition, SLD5 suppressed VSV replication in vitro and in vivo, and enhanced type Ⅰ interferon signalling. Taken together, our results suggest that targeting SLD5 by M protein might be a common strategy used by multiple enveloped RNA viruses to block host cell cycle. Our findings provide new mechanistic insights for virus to manipulate cell cycle progression by hijacking host replication factor SLD5 during infection.